Metal-free formal carbon–halogen bond insertion: facile syntheses of 3-halo 3, 3′-disubstituted oxindoles and spirooxindole-γ-butyrolactones. Issue 51 (12th June 2017) - Zhou, Rong; Liu, Rongfang; Zhang, Kai; Han, Ling; Zhang, Honghui; Gao, Wenchao; Li, Ruifeng
Abstract : A metal-free carbon–heteroatom bond insertion of isatins into allylic and benzylic bromides/chlorides is reported. Abstract : A novel P(NMe2 )3 -mediated formal carbon–halogen bond insertion of isatins into allylic and benzylic bromides/chlorides has been realized, leading to a facile synthesis of 3-halo 3, 3′-disubstituted oxindoles. This reaction relies on the unique dual nucleophilic–electrophilic reactivity pattern of the Kukhtin–Ramirez adduct via a cascade SN 2–SN 2 process. It also represents a rare metal-free approach for carbon–halogen bond insertion. Upon treatment with trifluoroacetic acid, spirooxindole-γ-butyrolactones have been efficiently prepared from the corresponding insertion products.